The Influence of Population Size and Poverty on Economic Growth in Aceh Province - Mora Savira; Sonny Muhammad Ihsan Mangkuwinata; Denny Sumantri Mangkuwinata (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
This study is motivated by the dynamics of population and poverty in Aceh Province, which have the potential to influence regional economic growth. Increases in population and reductions in poverty do not always correspond with optimal acceleration of economic growth, necessitating an empirical study to understand the relationship among these three variables. The objective of this research is to analyze the influence of population size and poverty on economic growth in Aceh Province, both partially and simultaneously. This study employs a quantitative approach using secondary time-series data from 1995 to 2024, obtained from the Central Statistics Agency. The analysis is conducted using a multiple linear regression model, complemented by classical assumption tests and hypothesis testing. The results indicate that, partially, population size has a significant effect on economic growth, with a regression coefficient of 6.546. Similarly, poverty significantly affects economic growth, albeit with a lower coefficient of 1.079. Simultaneously, population size and poverty together have a significant impact on economic growth, with a coefficient of determination (R²) of 0.942. These findings suggest that increasing population and addressing poverty in an integrated manner are important factors in promoting economic growth in Aceh. This study recommends that local governments design balanced development policies, optimize demographic potential, and strengthen poverty alleviation programs to support sustainable economic growth.